2018
DOI: 10.1109/jphot.2018.2860251
|View full text |Cite
|
Sign up to set email alerts
|

Design of Low-loss and Highly Birefringent Porous-Core Photonic Crystal Fiber and Its Application to Terahertz Polarization Beam Splitter

Abstract: We present the design of a porous-core PCF with elliptical holes in the core that achieved low loss, high birefringence, and flattened dispersion for guiding terahertz waves. The finite element method is used to study the properties of the designed waveguide in detail: effective material loss, birefringence, confinement losses, and dispersion. Simulation results show that the proposed structure exhibits simultaneously high modal birefringence of 1.32 × 10 −2 and a flattened dispersion over a broadband of 1.28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Effective area basically defines the confinement area of fundamental mode in the core of fiber, and it can be numerically investigated using Eq. (10). From Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Effective area basically defines the confinement area of fundamental mode in the core of fiber, and it can be numerically investigated using Eq. (10). From Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This commercial software makes the numerical analysis using full-vectorial finite element method (FEM). In addition, a rectangular perfectly matched layer (PML) boundary condition was introduced just at the outside of the cladding to absorb the electromagnetic signals propagating towards the core [37,47]. The PML is the most efficient absorption boundary condition, which helps to improve the numerical analysis and avoid possible sources of error [47,48].…”
Section: Design Of the Proposed Sensormentioning
confidence: 99%
“…The thickness of the PML is an important parameter due to its great impact on the simulation results. Therefore, we carry out the convergence test and found that proposed sensor provides the optimal results at a PML thickness above 10% of the total size of the sensor structure [37,49].…”
Section: Design Of the Proposed Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum element size in mesh is set five times smaller than the working wavelength. A cylindrical perfectly matched layer (PML) boundary condition, with a thickness of 1.55 µm was used to absorb the scattered electromagnetic waves towards the surface [52]. With these conditions, the total number of domain elements in the mesh was 68,278 with 4,530 boundary elements.…”
Section: Working Principlementioning
confidence: 99%